서울시내 일부 국민학교 학생의 성장발달 및 비만요인 분석 - 최영이 (연세대학교 보건대학원, 1989)
[한글] 이 연구는 국민하교 어린이의 성장발달 및 비만에 영향을 미치는 요인을 분석하였다. 조사대상은 서울시내 2개 사립국민하교 6학년 어린이 391명과 어머니 327명이며, 신체발육 조사는 건강기록부를 이용하였고 비만에 관련된 사항은 설문지를 이용하여 조사하였다. 자료의 분석에서 신장과 체중을 이용하여 Body Mass Index(BMI), Rohror Index(RI), Weight-for-length Index(WLI)를 산출하였고, WLI 120 이상자를 비만군으로 하고 WLI 109 이하를 일반군으로 구분하여 X**2-test, t-test로 두군의 차이를 검증하였고, 비만요인분석을 위해서 다중회귀분석을 시행하였다. 1) 1학년에서 BMI 90% 이상인 군에 속하는 어린이가 5학년에서 같은 군에 포함되는 율은 50.0%이었으며, WLI 120 이상을 기준으로 하는 경우 같은 군에 포함되는 율은 80.0%이었다. 2) WLI 120% 이상을 비만으로 정의 할 때, 비만 발생정도는 1학년 5.5%, 2학년 7.0%, 3학년 9.4%, 4학년 10.6%, 5학년 12.9%이었다. RI 160 이상을 기준으로 했을 때는 각각 3.1%, 3.7%, 3.9%, 7.1%, 8.3%로 학년의 증가에 따라 비만발생정도가 증가하였다. 3) 비만군과 일반군의 운동 상황에 대한 조사에서는 두군의 1일 TV시청시간, 좋아하는 운동, 여가시간 활용태도, 활동정도 등이 유의한 차가 있었다. 식습관에서는 식사의 규칙성, 식사속도가 두군간에 유의한 차이를 보였으며, 결식이유도 두군간에 차이를 보였다. 4) 조사아동에 대한 어머니의 관심도는 비만군의 어머니가 운동이나 식사지도에 많은 관심과 주의를 하였다. 5) 부모의 비만지수는 비만군의 아버지의 비만도가 일반군에 비해 유의하게 높았다. 비만정도를 유의하게 설명할 수 있는 변수는 아버지의 비만도, 여가시간 활용태도, 식사의 규칙성, 식사속도, 성, 활동정도, 어머니의 비만도 등이 였으며 이들 요인으로 비만정도 를 26.0% 설명할 수 있었다. A study on the physical development and the related factors influencing the obesity of elementary school students in Seoul Young Yee Choi Graduate School of Health Science and Management, Yonsei University (Directed by Prof. Myung Ho Kmi, M.D.) The purpose of this study was to analyze physical development and the important factors influencing the obesity among the elementary school students. Three hundreds and ninty one students from 2 private elementary schools including their mothers were surveyed using questionnaires. And their school health records were also used in the analysis. The height and weight use in calculating BMI, RI and WLI at the 1st grade through the 5th grade students were obtained from the school health records. From the data WLI value of over 120 was classified as the obese groups and under 109 as normal groups. Percentages, X**2-test and t-test were used to compare the characteristics of the two groups and multiple stepwise regression was used for the etiology analysis, respectively. The rusults of this study were shown as follows: 1) The percentage agreements of over 90% BMI body types in the 1st and the 5th grade showed 50.0%; and over 120 WLI body types was 80.0%. 2) The prevalence of obesity was 5.5% of the 1st grade, 7.0% of 2nd, 9.4% of 3rd, 10.6% of 4th, and 12.9% of the 5th grade. RI 160 and over for each grade were 3.1%, 3.7%, 3.9%, 7.1%, and 8.3%, respectively. Prevalence of obesity showed increasing tendency with school age. 3) There were significant differences in the following characteristics between two groups; such as hour of watching TV, preference of sports, attitude towards using one's leisure time, degree of activity, dietary habit, eating rate, and the reason for skipping meals. 4) Regarding physical exercises and eating behavior, the mothers of the obese groups gave greater attention than mothers of normal groups. 5) Fathers' BMI of obese groups were significantly higher than those of normal. Main factors affecting obesity account for the father's BMI, attitude toward using one's leisure time, dietary habit, eating rate, sex, degree of activity and mother's BMI. These variables explained 26.0% of the obesity. [영문] The purpose of this study was to analyze physical development and the important factors influencing the obesity among the elementary school students. Three hundreds and ninty one students from 2 private elementary schools including their mothers were surveyed using questionnaires. And their school health records were also used in the analysis. The height and weight use in calculating BMI, RI and WLI at the 1st grade through the 5th grade students were obtained from the school health records. From the data WLI value of over 120 was classified as the obese groups and under 109 as normal groups. Percentages, X**2-test and t-test were used to compare the characteristics of the two groups and multiple stepwise regression was used for the etiology analysis, respectively. The rusults of this study were shown as follows: 1) The percentage agreements of over 90% BMI body types in the 1st and the 5th grade showed 50.0%; and over 120 WLI body types was 80.0%. 2) The prevalence of obesity was 5.5% of the 1st grade, 7.0% of 2nd, 9.4% of 3rd, 10.6% of 4th, and 12.9% of the 5th grade. RI 160 and over for each grade were 3.1%, 3.7%, 3.9%, 7.1%, and 8.3%, respectively. Prevalence of obesity showed increasing tendency with school age. 3) There were significant differences in the following characteristics between two groups; such as hour of watching TV, preference of sports, attitude towards using one's leisure time, degree of activity, dietary habit, eating rate, and the reason for skipping meals. 4) Regarding physical exercises and eating behavior, the mothers of the obese groups gave greater attention than mothers of normal groups. 5) Fathers' BMI of obese groups were significantly higher than those of normal. Main factors affecting obesity account for the father's BMI, attitude toward using one's leisure time, dietary habit, eating rate, sex, degree of activity and mother's BMI. These variables explained 26.0% of the obesity.
보건학과/석사